A population-based audit of surgical practice and outcomes of oncoplastic breast conservations in Scotland – An analysis of 589 patients. Issue 7 (July 2018) - Romics, Laszlo; Macaskill, E. Jane; Fernandez, Teresa; Simpson, Louise; Morrow, Elizabeth; Pitsinis, Vassilis; Tovey, Sian; Barber, Matthew; Masannat, Yazan; Stallard, Sheila; Weiler-Mithoff, Eva; Malyon, Andrew; et al.
Abstract: Introduction: Current evidence for oncoplastic breast conservation (OBC) is based on single institutional series. Therefore, we carried out a population-based audit of OBC practice and outcomes in Scotland. Methods: A predefined database of patients treated with OBC was completed retrospectively in all breast units practicing OBC in Scotland. Results: 589 patients were included from 11 units. Patients were diagnosed between September 2005 and March 2017. High volume units performed a mean of 19.3 OBCs per year vs. low volume units who did 11.1 (p = 0.012). 23 different surgical techniques were used. High volume units offered a wider range of techniques (8–14) than low volume units (3–6) (p = 0.004). OBC was carried out as a joint operation involving a breast and a plastic surgeon in 389 patients. Immediate contralateral symmetrisation rate was significantly higher when OBC was performed as a joint operation (70.7% vs. not joint operations: 29.8%; p < 0.001). The incomplete excision rate was 10.4% and was significantly higher after surgery for invasive lobular carcinoma (18.9%; p = 0.0292), but was significantly lower after neoadjuvant chemotherapy (3%; p = 0.031). 9.2% of patients developed major complications requiring hospital admission. Overall the complication rate was significantly lower after neoadjuvant chemotherapy (p = 0.035). The 5 year local recurrence rate was 2.7%, which was higher after OBC for DCIS (8.3%) than invasive ductal cancer (1.6%; p = 0.026). 5-year disease-free survival was 91.7%, overall survival was 93.8%, and cancer-specific survival was 96.1%. Conclusion: This study demonstrated that measured outcomes of OBC in a population-based multi-centre setting can be comparable to the outcomes of large volume single centre series.